2011
DOI: 10.1007/s00281-011-0296-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of Staphylococcus epidermidis infections

Abstract: Staphylococcus epidermidis is the most important member of the coagulase-negative staphylococci and one of the most abundant colonizers of human skin. While for a long time regarded as innocuous, it has been identified as the most frequent cause of device-related infections occurring in the hospital setting and is therefore now recognized as an important opportunistic pathogen. S. epidermidis produces a series of molecules that provide protection from host defenses. Specifically, many proteins and exopolymers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
197
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(210 citation statements)
references
References 138 publications
(152 reference statements)
1
197
0
6
Order By: Relevance
“…Previous reports have shown that MALDI-TOF MS is a reliable method to identify Staphylococcus at the species level; however, questions regarding the impact of such methods in clinical settings remain uncertain (9). Staphylococcus epidermidis is probably the major CoNS species causing nosocomial infections, although other CoNS, such as S. lugdunensis, S. schleiferi, and S. saprophyticus, have been reported as even more pathogenic in a range of both nosocomial and communityacquired infections (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Previous reports have shown that MALDI-TOF MS is a reliable method to identify Staphylococcus at the species level; however, questions regarding the impact of such methods in clinical settings remain uncertain (9). Staphylococcus epidermidis is probably the major CoNS species causing nosocomial infections, although other CoNS, such as S. lugdunensis, S. schleiferi, and S. saprophyticus, have been reported as even more pathogenic in a range of both nosocomial and communityacquired infections (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Investigation of biofilms occurring in a public drinking water distribution system in Romania revealed the presence of S. warneri and S. vitulinus [43]. Based on results of those studies, S. epidermidis -an important nosocomial opportunistic pathogen [44,45] -is the most frequently isolated species among staphylococci occurring in the aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus epidermidis is part of the human epithelia microflora and usually has a benign relationship with the host. Colonization with S. epidermidis contributes to the maintenance of a healthy skin flora by competition with potentially harmful microorganisms (2). In the recent decades, however, with increasing use of indwelling or implanted medical devices and the increase of multi-morbid, elderly, and immunocompromised patients, S. epidermidis has emerged as an important opportunistic pathogen responsible for hospital-acquired infections, especially biofilm-associated infections (1).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus epidermidis is one of the often encountered biofilm-producing bacteria and the establishment of S. epidermidis as a nosocomial pathogen mainly depends on biofilm formation (2). Polysaccharide intercellular adhesin (PIA) encoded by icaADBC operon is a mediator of biofilm formation in S. epidermidis (3).…”
Section: Introductionmentioning
confidence: 99%